(untitled) (Academicia Globe: Inderscience Research, 2021)
This article refers to the cutting processing and cutting processing of resin materials and the dressing of the shavings. When cutting, the cutting modes are how they are, and the cutting modes are prepared in the direction of the effect on the surface cleanliness.